CIPP Evaluation Model: Online In-service Teachers Training Program Conducted at English Language Education Study Program of Bengkulu University - Kasmaini, Kasmaini; Hamzah, Syukri; Winarto, Hadi (ENGLISH FRANCA : Academic Journal of English Language and Education, 2023)
This study aims to evaluate the implementation of the teacher professional education program for teachers in positions that are carried out online at the Faculty of Education and Teacher Training at the University of Bengkulu. This research was conducted from September to November 2022 as a qualitative descriptive study. The instruments used were documentation, interviews, and questionnaires. Interviews were conducted with lecturers, PPG students, tutors, and school/madrasah policyholders. The questionnaire is used to see student or participant responses to the implementation of the online learning process. The CIPP evaluation model used focuses on evaluating the context, inputs, processes, and products. Sources of data were obtained from program managers, supervisors, PPG students, school/madrasah principals, tutors, and monitoring and evaluation (monev) results. The data analysis technique used is descriptive data analysis by interpreting the data from each evaluated aspect, then compared with predetermined criteria. Viewed from the context aspect, the FKIP UNIB PPG study program is under the Standard Operating Procedures as the organizer of PPG activities. From an input perspective, the PPG study program is supported by adequate human resources. All lecturers involved, educational staff, tutors, and students are by the program implementation guidelines. In the process aspect, the PPG FKIP UNIB study program has carried out PPG program activities following the SOP. This is evidenced by all the stages carried out in a structured and well-organized manner so that starting from the preparation and implementation processes go well. All well-patterned processes have an impact on the products produced. Referring to the high passing percentage of PPG participants and achieving a passing percentage proves the success of the PPG FKIP UNIB study program in implementing the PPG program. Other successes of the PPG study program have been accredited Superior.Â